Peroral cholangioscopy for non-invasive papillary cholangiocarcinoma with extensive superficial ductal spread - Wakai, Toshifumi (World J Gastroenterol, 2005)
Papillary carcinoma arising from the extrahepatic bile duct often shows superficial ductal spread. We report herein the case of a patient with extensive superficial spread of non-invasive papillary cholangiocarcinoma, which was depicted with peroral cholangioscopy. A 65-year-old woman presented with the sudden-onset of severe epigastric pain. Ultrasonography revealed acute acalculous cholecystitis. Endoscopic retrograde cholangiography found small protruding lesions around the confluence of the cystic duct, suggestive of a cholangiocarcinoma. As the contour of the middle and upper bile ducts it was slightly irregular on the cholangiogram, the presence of superficial ductal spread was suspected. Peroral cholangioscopy revealed small papillary lesions around the confluence of the cystic duct and fine granular mucosal lesions in the middle and upper bile ducts and the right hepatic duct, suggesting a superficially spreading tumor. A right hepatectomy with bile duct resection was performed and no residual tumor was found. Histological examination revealed a non-invasive papillary carcinoma arising from the cystic duct with extensive superficial spread. Our experience of this case and a review of the literature suggest that a fine granular or fine papillary appearance of the ductal mucosae on cholangioscopy indicates superficial spread of papillary cholangiocarcinoma, for which peroral cholangioscopy is an efficient diagnostic option.